Growth and wear of incisor and cheek teeth in domestic rabbits (Oryctolagus cuniculus) fed diets of different abrasiveness. Issue 5 (2nd April 2014) - Müller, Jacqueline; Clauss, Marcus; Codron, Daryl; Schulz, Ellen; Hummel, Jürgen; Fortelius, Mikael; Kircher, Patrick; Hatt, Jean‐Michel
ABSTRACT Although patterns of tooth wear are crucial in palaeo‐reconstructions, and dental wear abnormalities are important in veterinary medicine, experimental investigations on the relationship between diet abrasiveness and tooth wear are rare. Here, we investigated the effect of four different pelleted diets of increasing abrasiveness (due to both internal [phytoliths] and external abrasives [sand]) or whole grass hay fed for 2 weeks each in random order to 16 rabbits (Oryctolagus cuniculus) on incisor and premolar growth and wear, and incisor and cheek tooth length. Wear and tooth length differed between diets, with significant effects of both internal and external abrasives. While diet abrasiveness was linked to tooth length for all tooth positions, whole forage had an additional effect on upper incisor length only. Tooth growth was strongly related to tooth wear and differed correspondingly between diets and tooth positions. At 1.4–3.2 mm/week, the growth of cheek teeth measured in this study was higher than previously reported for rabbits. Dental abnormalities were most distinct on the diet with sand. This study demonstrates that concepts of constant tooth growth in rabbits requiring consistent wear are inappropriate, and that diet form (whole vs. pelleted) does not necessarily affect cheek teeth. Irrespective of the strong effect of external abrasives, internal abrasives have the potential to induce wear and hence exert selective pressure in evolution. Detailed differences in wear effects between tooth positions allow inferences about the mastication process. Elucidating feedback mechanisms that link growth to tooth‐specific wear represents a promising area of future research. J. Exp. Zool. 321A:283–298, 2014. © 2014 Wiley Periodicals, Inc.